STRATEGI PEMASARAN ONLINE MENGGUNAKAN FACEBOOK UNTUK MENINGKATKAN KEBERHASILAN BISNIS UMKM DI KOTA TERNATE - Nurwinta Nani; Faisal Y Habsyi; Anhar Drakel (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2023)
The increasingly dynamic global economic development demands improvements in the quality of human resources through education, including in the field of economics. However, students' low understanding of basic economic concepts remains a major problem in various educational institutions. This study aims to analyze the effectiveness of the implementation of the Problem Based Learning (PBL) learning model in improving high school students' understanding of economic concepts. The research method used was a quasi-experimental study with a pretest-posttest control group design. The study sample consisted of two classes of eleventh grade social studies (11 IPS) at a public high school in Yogyakarta, which were selected purposively. Data were collected through a conceptual understanding test and analyzed using a t-test. The results showed a significant difference between the average posttest scores of students who participated in learning with the PBL model compared to students who participated in conventional learning. The PBL model has been proven to improve understanding of economic concepts more effectively because it encourages students to think critically, collaboratively, and contextually in solving everyday economic problems. In conclusion, the implementation of the Problem Based Learning model has a positive influence on improving students' understanding of economic concepts. This study recommends the application of PBL as an alternative learning strategy in economics education, especially at the secondary school level.